Penerapan Pengendalian Hama Terpadu (PHT) Tikus Sawah (Rattus argentiventer) di Desa Ketawang Kecamatan Gondang Kabupaten Nganjuk - Dwi Haryanta; Marmi Marmi; Pramita Laksitarahmi Isrianto; Sunaryo Sunaryo; Dina Chamidah (JURNAL PENGABDIAN MASYARAKAT AKADEMISI, 2026)
Rat pest (Rattus argentiventer) is one of the main constraints in rice cultivation, potentially causing crop failure of up to 60–70% if not properly controlled. This community service activity aims to improve the knowledge and skills of farmers in Ketawang Village, Gondang District, Nganjuk Regency, East Java, in implementing Integrated Rat Pest Control (PHT). The methods used were Participatory Rapid Rural Appraisal (PRRA) and Rapid Rural Appraisal (RRA), actively involving village officials and farmer groups. Activities included initial discussions, extension services, and field evaluations. The results of the activity showed that farmers gained a better understanding of the concept of integrated pest management (IPM) for rice field rat pests. The implementation of the IPM concept prioritizes technical cultural control techniques and biological control, namely environmental sanitation, simultaneous planting, utilization of natural enemies (Tyto alba owls), mass grouping, fumigation, and the use of poison bait. This program is expected to disrupt the rat breeding cycle, reduce farmers' economic losses, and support local food security in Ketawang Village.